Load balance multicast routing algorithms on overlay network - ZHANG Xiao-yu; ZHANG Guang-zhao (Tongxin xuebao)
Overlay networks had been recently developed to support multicast framework.Specially,overlay architec-tures based on proxies and leased lines could provide applications with optimal performance in terms of bandwidth,reliability,delay guarantee,etc.A balanced multicast routing algorithm for these proxy-based overlay architectures was proposed to utilize the network resources efficiently while keeping the delay guarantee for each multicast session.First,the routing problem was modeled as a delay-constraint Steiner tree problem.Then,a balanced solution with the aid of precomputing was proposed.The precomputing performed once with high complexity.However,its outcome was used multiple times in the later low complexity tree forming algorithm.Hence,the overall complexity was low-ered.Extensive simulations show that the multicast routing algorithm provides superior performance with respect to other heuristics.